Context-based Integrated Suites for News Delivery System - S.M.F.D, Syed Mustapha (2011)
The number of mobile phone users has grown surpassing the PC users due to its mobility and handiness, increasing of its processing power and memory, continuous growth of its applications and operating system’s capabilities. Calendar is one of the common applications that are made available to these devices. Users are more dependent in using calendar to plan their daily activities. In a long term, the aggregation of these accounts can be the source of information in analyzing an individual’s favorites, routines events, social contacts or personal beliefs. We developed a system to deliver the Mobile News Content (MNC) to individuals based on the information extracted from the calendar. The key capability of MNC is the ability to deliver news relevant to the current context of the individual with respect to the event, social and time. We propose an integrated suite that consists of event-capturing engine, news content controller and context calendar to enhance the news delivery capabilities. The event-capturing engine senses the actual activity that takes place and synchronizes with the context calendar automatically. The news content controller manages the delivery of news based on the event being sensed and the planned activity extracted from the context calendar. This paper discusses the components of the suite, system architecture and the system workflow of the suite